Design of heater for microscale heat transfer in macro geometries - Ong, Clarence Jie Feng (2017)
There are many success in utilising microchannel to enhance heat transfer capabilities for heat dissipation purpose. However, it will be expensive to fabricate such microchannels in macro geometries. This spurs research on microscale heat transfer in macro geometries. In previous research, the use of implementing geometric profile on inserts which are placed concentrically into a cylindrical heater that creates an enhanced microchannel. With the aid of perturbation of the fluid flow, it improves the heat transfer greatly. This study aims to move a step further, through the increasing of both the perturbation of the fluid flow and heat transfer area by introducing geometric profiles on the inner side of the heater. The numerical simulations were ran at 3 to 7 L/min with intervals of 1 L/min. The heat supplied is constant at 1000 W for all cases. Thermal adhesives were also proposed to fill the air gap that is present between the copper heater and the cooper block with profile. Different materials for the heater is also tested to determine which material is more suitable. The 16.8% increase in heat transfer area sees a maximum 31% enhancement in thermal performance in relation to the profile on insert microchannel. With the same thermal performance, the pumping power requirement is reduced by 37% as compared with the profile on insert. Thermal adhesives were also deemed not suitable for usage. Ceramics was determined to be the most suitable material based on the materials tested. Despite the fact that this study justifies the increase in heat transfer area together with flow perturbations will enhance the heat transfer capabilities, experiments need to be carried out to validate the results presented. Furthermore, other geometric profiles designed using the Constructal theory can be tested. With this primary research, a complete design for the heater can be developed in the future.